Intestinal and Tracheal Parasites of Poultry - Gary D. Butcher; Michael A. Davis (EDIS)
A parasite is defined as an animal or plant that derives sustenance and/or protection by living in or on another animal or plant called the host. Intestinal and tracheal parasites of poultry are commonly referred to as “worms,” although this term is technically not correct. These parasites can cause chickens in a flock to appear unthrifty, which often leads to secondary complications. In some cases, the parasites can cause mortality in the flock. Frequent inspection of the flock for signs of illness is the best management tool for identifying when these parasites are a problem. This revised 3-page fact sheet was written by Gary D. Butcher and Michael A. Davis, and published by the UF Department of Animal Sciences, February 2014.